CELEBRITY ENDORSER DAN BRAND IMAGE (STUDI KORELASIONAL MENGENAI CELEBRITY ENDORSER DAN BRAND IMAGE TEPUNG BUMBU SASA DI BENAK KONSUMEN DI DIY) - , ASTRID PARAMITHA W ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Nowadays celebrities are developed into an important content and staple in Indonesia. It can be seen from many kinds of infotainment programs in several television stations, even infotainment show can be broadcast up to three times a day. This fact proves that the community has a high interest in the lives of celebrities. Popularity of celebrities is undeniably become a phenomenon of its own since become one of the focus of publicity in the mass media. Seen this phenomenon many manufacturers of goods or services realize that celebrities have a power to influence people. The power that owned by celebrities then used as an endorser by the manufacturer of each ad in order to communicate and establish their brand identity and their brand image to determines the product or service that being advertised. In the instant seasoning competition that has entered to red ocean level, brand communication of Sasa does the promotion strategy by collaborating with the artist as celebrity endorser, it is Chef Farah Quinn who already known as a professional chef. This study is intended to look at how high the celebrity endorser correlate to the brand image of Seasoning Flour Sasa in the minds of consumers. This research was conducted using S-O-R theory as the basis of the communication process. This theory emphasizes the organism (O) which received stimulus (S) in order to get a response or feedback (R) that are expected. From the survey, it is known that there are three factors that must be owned by a celebrity endorser are source credibility, source attractiveness and source power. These three factors are going to affect the assessment of respondents (organisms) in generating brand image. So respondents (O) have an important role in this study. This study proves the correlation between celebrity endorser with the brand image that represented.